Students’ Perception of the Importance of Facial Authentication Software in Moodle Tools. - Guillén-Gámez, Francisco David; Bravo-Agapito, Javier; García-Magariño, Iván (TEMPUS, 2017)
Nowadays, the use of facial authentication software in distance education could help to guarantee the proper login of students in the Learning Management Systems. Also, facial software utilization in online activities will probably identify students and prevent cheating. Thus, the current research analyzes the suitability of introducing a facial authentication software application in different LMS tools. In order to reach this goal, the perceptions of 67 master students were analyzed. Students were divided into two groups. The facial software was applied to the first group at the same time when this group did their coursework using Tests, Glossaries, and LessonsMoodle tools. The second group did their course work using Forums, Task mailboxes, and Databases Moodle tools without the surveillance of the facial software. Then, both groups were surveyed by a questionnaire related to the students’ perception about using facial authentication software in Moodle tools. The data analysis revealed that the Moodle tools in which the implantation of facial authentication software would be important are Tests, Glossaries and Lessons.
Keywords: Reconocimiento facial (Informática); Educación - Innovaciones tecnológicas; E-learning; Moodle; Facial authentication; Online learning; Moodle tools